Strategies for improving adoption of soil-fertility technologies in Rwanda - Bizimana, Claude (International Food Policy Research Institute, 2013)
Factors influencing the adoption of soil-fertility technologies (measured by soil testing and use of chemical fertilizers) in key areas of the southern province, where soil-fertility problems are prevalent and potentially impact the performance of the coffee sector, were studied. The results of the analysis, using household survey data, principal components, and linear discriminant analysis, show that farm fragmentation, age, wealth, and education are the most important factors influencing adoption of the two soil-fertility technologies.